Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1155/2016/6756859
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Interval between Neoadjuvant Chemoradiotherapy and Surgery on Oncological Outcome for Rectal Cancer: A Systematic Review and Meta-Analysis

Abstract: Aim. To evaluate the influence of interval between neoadjuvant chemoradiotherapy (NCRT) and surgery on oncological outcome. Methods. A systematic search was conducted in PubMed, the Cochrane Library, and Embase databases for publications reporting oncological outcomes of patients following rectal cancer surgery performed at different NCRT-surgery intervals. Relative risk (RR) of pathological complete response (pCR) among different intervals was pooled. Results. Fifteen retrospective cohort studies representing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 44 publications
2
26
0
1
Order By: Relevance
“…One of the confounding factors that will affect the rectal tumour response rate is the waiting time from cessation of neoadjuvant CRT to surgery. Supporting evidence was reported in two recent meta‐analyses, in which a longer interval of time to surgery (ideally 6–8 weeks) resulted in higher pCR rates compared with those who had surgery at 4–6 weeks with no added response rate beyond 9 weeks . This is not an issue in the current study as the majority reported interval times of 6–8 weeks after neoadjuvant CRT, with the exception of four studies, which reported minimum time to surgery of 4 weeks .…”
Section: Discussionsupporting
confidence: 83%
“…One of the confounding factors that will affect the rectal tumour response rate is the waiting time from cessation of neoadjuvant CRT to surgery. Supporting evidence was reported in two recent meta‐analyses, in which a longer interval of time to surgery (ideally 6–8 weeks) resulted in higher pCR rates compared with those who had surgery at 4–6 weeks with no added response rate beyond 9 weeks . This is not an issue in the current study as the majority reported interval times of 6–8 weeks after neoadjuvant CRT, with the exception of four studies, which reported minimum time to surgery of 4 weeks .…”
Section: Discussionsupporting
confidence: 83%
“…Previous retrospective analysis due to the time interval of chemoradiation and surgery of rectal cancer have been made. All of them gained evidence for an increased rate of pCR by prolonging the time interval between neoadjuvant treatment and surgery without affecting perioperative morbidity [8][9][10][22][23][24][25]. These studies analyzed patients from the United States, the Netherlands or Belgium, whereas the number of patients was partly low (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The German guidelines for colorectal cancer recommend the oncological resection 6 to 8 weeks after completed preoperative chemoradiotherapy [7]. Recent studies have shown that a prolonged interval leads to higher rates of pathological complete response (pCR) and that this my even take longer than 16 weeks [8][9][10][11]. In addition, it was shown, that additional inclusion of chemotherapy cycles in the interval between radiochemotherapy and surgery enhance complete response rate without affecting surgical morbidity [12].…”
Section: Introductionmentioning
confidence: 99%
“…The highest pCR rates were recorded in patients operated on beyond eight weeks after the end of chemoradiotherapy, which was associated with an approximately 49% higher chance for pCR compared to patients who were operated on earlier. Prolonging the interval beyond 10 or 12 weeks did not offer further advantages and also didn't affect survival or rate of sphincter spearing procedures [20].…”
Section: Response To Preoperative Chemoradiotherapymentioning
confidence: 94%
“…According to their results, pCR improved by 5.8% when the interval to surgery was longer than six to eight weeks, without compromising OS and DFS and with similar complication rates and sphincter preservation. A systematic review and meta-analysis by Wang et al [20] included 15 retrospective studies with 4,431 patients and pCR ranging from 8.3% to 28%. The highest pCR rates were recorded in patients operated on beyond eight weeks after the end of chemoradiotherapy, which was associated with an approximately 49% higher chance for pCR compared to patients who were operated on earlier.…”
Section: Response To Preoperative Chemoradiotherapymentioning
confidence: 99%